MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA “SERASIK” UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS III DI SDN 5 RAHTAWU - Fitri Wahyuningtiyas; Dwi Amelia Noor; Putri Nor Aini; Fitriyah Amaliyah (STKIP Subang, 2026)
The low level of elementary school students' mathematical conceptual understanding remains a major issue in mathematics learning, particularly in the topic of angles. This condition is caused by teacher-centered instruction, limited active student participation, and the lack of engaging instructional media. This study aimed to examine the effect of implementing the Problem-Based Learning (PBL) model assisted by the